Environmental impact assessment of traditional Udo cultivation methods in Sanda city, Hyogo prefecture - Nagano, Kazuo; Oshio, Kengo (JAPANESE JOURNAL OF BIOMETEOROLOGY, 2025)
Life cycle assessment was conducted for traditional Udo (Aralia cordata) cultivation in straw thatched hut and current mainstream plastic greenhouse in Sanda city. Calculations were made using the accumulated method based on IDEA v2.3, a life cycle inventory database. The results showed that the CO2 emissions, a cause of climate change, was 4.50 kg-CO2eq per kg of Udo in thatched hut cultivation, while it was 1.61 times higher, 7.25 kg-CO2eq, in plastic greenhouse cultivation. In addition, the thatched hut cultivation was superior in a total of 10 impact categories, including resource depletion, eutrophication, and photochemical oxidant. On the other hand, the yield was only 76.9 % of that of the plastic greenhouse cultivation and the total labor hours were 41.2 hours longer.